MAD MEN: LOOKING BACK IN WONDER - CÎMPEAN, Raluca Lucia (Studia Universitatis Babeș-Bolyai Philologia, 2017)
Mad Men: Looking Back in Wonder. This study focuses on the literary roots of the popular television series Mad Men, namely Sloan Wilson’s 1955 novel The Man in the Gray Flannel Suit and Richard Yates 1961 debut novel Revolutionary Road, and on the genuine dialogue in which they engage at the level of character portrayal and argument. Their intertextual triangle offers an illustrative example of cultural recycling and re-contextualizing of 1960’s domestic and professional dilemmas for a twenty-first century medium and public. The success and longevity of Mad Men are raised upon the constant appeal of this tumultuous decade for contemporary audiences and capitalize on the universality of the issues it foregrounded. REZUMAT. Mad Men: cu privirea peste umăr. Acest studiu analizează rădăcinile literare ale popularului serial de televiziune Mad Men, şi anume romanul lui Sloan Wilson The Man in the Gray Flannel Suit (1955) şi cel de debut al lui Richard Yates, Revolutionary Road (1961), şi dialogul lor la nivelul portretizării personajelor şi al argumentului general. Acest triunghi intertextual oferă un exemplu de reciclare culturală şi de recontextualizare a dilemelor profesionale şi domestice ale anilor ’60, pentru un public şi un medium de reprezentare din secolul al XXI-lea. Succesul şi longevitatea serialului se bazează pe fascinaţia pe care o exercită această furtunoasă decadă asupra audienţei contemporane şi valorifică universalitatea problematicilor avansate. Cuvinte-cheie: dialog cultural, intertextualitate, anii ’60, cultură domestică, roluri de gen, melodramă, tragedie.